Partial Substitution of Margarine with Avocado Fruit Puree for Healthy Pound Cake Preparation using Various Flour Types and Baking Methods - Wilbur Donald Raymond Pokatong; Tiffany Nathalie (Dept. of Chemical Engineering, Diponegoro University, 2021)
Avocado (Persea americana) is known to have high dietary fiber and monounsaturated fatty acids which can reduce low density lipoprotein (LDL); thus, reduced risk of heart attack. The research objective was to partially substitute margarine with avocado puree in the preparation of pound cakes to reduce the saturated fat and increase the nutritional values. The pound cakes were prepared with five different ratios of avocado puree to margarine which were 0:1, 1:3, 1:1, 3:1, and 1:0 using three types of flour (all-purpose, cake, or bread flour) and baked using two methods (oven and microwave baking). Results showed that avocado contains 81.37±1.38 (%, wb), 53.09±3.64 (%, db), 6,98±0.49 (%, db), 34.57±3.63 (%, db), and 5.36±0.49 (%, db) of moisture, fat, protein, carbohydrate, and ash, respectively. From each type of flour, one pound-cake was selected based on its physical properties i.e. firmness, volume expansion, L* value, and ohue. Selected pound cakes were further evaluated with scoring and hedonic tests by 70 panelists to observe its consumer acceptance and selected the best pound cake from each type of baking methods (oven and microwave baking). The results showed that oven-baked pound cake with avocado puree to margarine ratio 1:1 prepared with cake flour and microwave-oven-baked pound cake with avocado puree to margarine ratio 1:1 prepared with bread flour exhibited the highest acceptance with overall hedonic values of 4.96±1.18 and 4.83±1.09, respectively. However, considering the time needed for baking and that the microwave baked pound cakes exhibiting higher protein, the pound cake baked in the microwave oven is more preferrable for further commercial manufacture.Keywords: avocado;baking; fat-substitution;flour types, pound-cake